ALIGNMENT OF 6TH GRADE LARGE-SCALE ASSESSMENT CONSTRUCTS WITH THE REVISED CURRICULUM FRAMEWORK - Pestovs, Pāvels; Namsone, Dace; Čakāne, Līga; Saleniece, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
One of the goals of the National Development Plan 2014-2020 is to reduce the proportion of students with low cognitive skills, and at the same time increase the proportion of students with higher level cognitive skills. In line with those goals, the National Centre for Education is implementing the project “Competency-based approach to curriculum”, funded by the European Social Fund. The purpose of the research described in this article is to find out to what extent the current large-scale national assessments for 6th Grade are coherent with the new curriculum and what improvements are needed for aligning the national assessments with the national curriculum. The theoretical framework of the research is developed by analysing the frameworks of the programme for international student assessment (PISA), trends in international mathematics and science study (TIMSS), progress in international reading literacy study (PIRLS), as well as the framework of the revised national curriculum in Latvia. National 6th Grade assessments of the year 2018 are analysed by using Classical test theory and Rasch model. The indicators of the test items are mapped according to the developed theoretical framework. Authors conclude that the national 6th Grade tests assess the elements of literacy, numeracy and scientific literacy. Students have a high level of performance in test items with low cognitive depths, but there is an insufficient number of test items with high cognitive depths, allowing pupils to demonstrate skills in new contexts, which is an essential goal of the new national curriculum. Further research is required on the use of data from the large-scale assessment in supporting and guiding student instruction and learning.